sistema preventivo de Don Bosco : Aportaciones para una acción tutorial - Gangoso, María Pilar (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 1999)
The aim of this article is to integrate the essence of the Salesian Order, as upheld in the "Preventive System" by Don Bosco, and the orientation, given for the reforms in the Spanish System of education within the framework of tutoring.